2010
DOI: 10.1097/hjh.0b013e32833e4fd8
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and survival in long-term hemodialysis patients with and without polycystic kidney disease

Abstract: Background In maintenance dialysis patients, low blood pressure (BP) values are associated with higher death rates when compared to normal to moderately high values. This “hypertension paradox” may be related to comorbid conditions. Dialysis patients with polycystic kidney disease (PKD) usually have a lower comorbidity burden and greater survival. We hypothesized that in PKD dialysis patients, a representative of a healthier dialysis patient population, high BP is associated with higher mortality. Methods Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…tertiles) of eGFR slope groups using KaplanMeier curves and unadjusted conditional Cox regression models. For each PS-matched analysis, several 'doubly robust' adjustment levels can be examined including minimally adjusted and case-mix adjusted models, as well as more comprehensive adjustment such as inclusion of laboratory and comorbidity status, as we have done in our recent studies [33,[56][57][58][59][60][61][62][63]. The PS method can primarily be used to account for confounding effects arising from differences in clinical characteristics of patients in whom transition to RRT occurs at different levels of eGFR.…”
Section: U S E O F P R O P E N S I T Y S Co R E S a N D I N V E R S Ementioning
confidence: 99%
“…tertiles) of eGFR slope groups using KaplanMeier curves and unadjusted conditional Cox regression models. For each PS-matched analysis, several 'doubly robust' adjustment levels can be examined including minimally adjusted and case-mix adjusted models, as well as more comprehensive adjustment such as inclusion of laboratory and comorbidity status, as we have done in our recent studies [33,[56][57][58][59][60][61][62][63]. The PS method can primarily be used to account for confounding effects arising from differences in clinical characteristics of patients in whom transition to RRT occurs at different levels of eGFR.…”
Section: U S E O F P R O P E N S I T Y S Co R E S a N D I N V E R S Ementioning
confidence: 99%
“…2 Whereas obesity is a risk factor for CKD, 3 many epidemiological studies have indicated inverse associations between obesity or other cardiovascular risk factors and mortality in patients with CKD or cardiac disease. 4,5 A higher death rate has been observed in patients with CKD who have a low, rather than a high, body mass index (BMI [calculated as the weight in kilograms divided by height in meters squared]), 6 blood pressure, 7 or serum concentrations of cholesterol 8 or homocysteine, 9 whereas high values of these risk factors are associated with improved survival. Other patient populations, including those with heart failure, 10 those with coronary artery disease, 5,11 and those of advanced age, 12 also exhibit this so-called obesity paradox.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…The creation of the national DaVita dialysis patient cohort has been described previously (15)(16)(17)(18)(19)(20)(21)(22). Demographic data and details of medical history were collected, with information on age, sex, race, type of insurance, marital status, presence of diabetes, height, body weight (to calculate averaged body mass index), dialysis modality (HD versus PD), and dialysis vintage.…”
Section: Clinical and Demographic Measuresmentioning
confidence: 99%